Efeitos das formulações nanoestruturadas de doxorrubicina e cisplatina em dispersão de óxido de grafeno reduzido no tratamento da progressão do câncer de bexiga Não-músculo invasivo - Villela, Renata Abreu [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Bladder cancer is the most common malignancy of the urinary tract. The recommended first-line treatment for non-muscle invasive bladder cancer (NMIBC) following transurethral resection, is an induction course plus maintenance with intravesical Bacillus Calmette-Guerin (BCG). However, BCG immunotherapy causes undesirable effects, which contributes to treatment interruption, increasing cancer index recurrence. In this context, graphene oxide (GO) and/or reduced graphene oxide (rGO) has attracted increasing interest in the field of biological detection, drug delivery and cancer therapies. Thus, the aim of this study was to characterize and to compare the antitumor effects of Doxorubicin (DOXO) and Cisplatin (CIS) functionalized in rGO on dispersion with Pluronic F-68 polymer to the treatment of NMIBC. Initially, the characterization of the compound guarantee its chemical properties. It was used 30 female Fischer 344 rats, consisting a control group of five animals (Group 1), which received 0.3 ml of saline 0.9% intraperitoneally (i.p.). The remaining animals received 1.5 mg/kg of N-methyl-N-Nitrosourea (MNU) intravesical (i.v.) and after four doses, they were divided into five groups: Cancer Group (Group 2), Cancer + rGO Group (Group 3), Cancer + rGO + CIS Group (Group 4), Cancer + rGO + DOXO Group (Group 5), Cancer rGO + CIS + DOXO Group (Group 6), which received, respectively: the same treatment as group 1; received 0.2 mL dose at a concentration of 0.2mg/ml; received 0.2 mL of rGO dispersion with 0.05mg CIS; received 0.2 mg of DOXO in 0.2 mL of the dispersion; received 0.2 mL of rGO dispersion with the same chemotherapy combinations that groups 4 and 5. All treatments were i.p., with weekly administration during six consecutive weeks. After 16 weeks of treatment, urinary bladders were collected for histopathological, immunohistochemical and biochemical analysis, and still, blood collected for performing biochemical analyzes to obtain ...

O câncer de bexiga é a malignidade mais comum do trato urinário. O tratamento mais estipulado atualmente para os casos de câncer de bexiga não-músculo invasivo (CBNMI) é uma ressecção transuretral associada à administração de dose intravesical de manutenção de Bacillus de Calmette-Guerín (BCG). Entretanto, a imunoterapia com BCG também causa efeitos indesejáveis, além de aumentar a taxa de recidiva da doença secundária à interrupção do tratamento. Nesse contexto, o óxido de grafeno (GO) e/ou o óxido de grafeno reduzido (rGO) têm atraído significativo interesse no campo da detecção biológica, drug delivery e nas terapias anti-tumorais. Assim, o objetivo deste estudo foi caracterizar e comparar os efeitos antitumorais da Doxorrubicina (DOXO) e da Cisplatina (CIS) funcionalizadas na dispersão rGO com polímero Pluronic® F-68 frente ao tratamento do CBNMI. Inicialmente, foi realizada a caracterização do composto de rGO para conhecer suas propriedades químicas. Foram utilizadas 30 ratas da variedade Fischer 344, sendo constituído um grupo controle de cinco animais (Grupo 1), os quais receberam 0,3 mL de solução fisiológica à 0,9% por via intraperitoneal (i.p.). Nos demais animais foram administradas doses de 1,5 mg/kg de N-metil-N-nitrosouréia (MNU) intravesical (i.v.) e, após quatro doses, foram divididos em cinco grupos: Grupo Câncer (Grupo 2), Grupo Câncer+rGO (Grupo 3), Grupo Câncer+rGO+CIS (Grupo 4), Grupo Câncer+rGO+DOXO (Grupo 5) e Grupo Câncer+rGO+CIS+DOXO (Grupo 6), os quais receberam respectivamente: mesmo tratamento do Grupo 1; dose 0,2mL na concentração de 0,2mg/mL de rGO; 0,2mL da dispersão rGO com CIS a 0,05mg; 0,2mg de DOXO em 0,2mL da dispersão e 0,2mL da dispersão com as mesmas concentrações de quimioterápicos que os Grupos 4 e 5. Todos os tratamentos foram por via i.p., com administração semanal durante seis semanas consecutivas. Após 16 semanas de...
Keywords: Biologia; Doxorrubicina; Cisplatina; Bexiga - Câncer; Bladder - Cancer